PENGARUH SYARIAH GOVERNANCE TERHADAP KINERJA BANK SYARIAH DENGAN LOYALITAS NASABAH SEBAGAI VARIABEL MEDIASI (STUDI PADA BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH DI PROVINSI RIAU) - Ressy Fitriasari; Kamaliah Kamaliah; Yesi Mutia Basri (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
This study aim to examines the impact of the implementation of syariah governance business to the performance of the banks syariah with loyality as mediation variabel in Riau Province. The dependent variable used in this research was the performance of the banks syariah is measured financial and non financial performance perspective used balanced scorecard. An independent variable in this research is syariah governance consisting of transparancy , professional, accountability, responsibility, fairness and syariah compliance. The mediation variable used in this research was the loyality costumer. Population in this study were general syariah-based bank (BUS) and syariah business unit (UUS) in the Province of Riau and as many as 49 BUS and UUS). Respondents in this study used top management , middle management and low management. As many as 196 questionnaire delivered to respondents and which could processed is 118 questionnaire. Analysis techniques used Structural Equation Model (SEM) bases on Partial Least Square (PLS) with the help Warp PLS 6.0 program. The results of testing shows are that transparancy, accountability, fairness had a significant effect on the loyality but responsibility, professional and syariah compliance no significant effect. Responsibility and professional had a significant effect on the performance of the syariah banks but transparancy, accountability, fairness and syariah compliance no significant effect. Loyality had a significant effect on the performance of the syariah banks. Transparancy, accountability and fairness had a significant effect on the performance of the syariah banks by loyalitay but responsibility, professional and syariah compliance no significant effect on performance of syariah banks by loyality.The results of the study contribute to as much as that good governance is the important thing in improving the performance of their status into syariah banks.